Assessment of the agronomic and nutritional characteristics of sorghum genotypes with and without brown midrib - Moura, Marielly Maria Almeida; Mizobutsi, Edson Hiydu; Pires, Daniel Ananias de Assis; Campos, Marcos Lopes de; Costa, Renê Ferreira; Pires Neto, Otaviano de Souza; Santos , Leandra Cristina Soares; Fernandes, Martielle Batista (Acta Scientiarum. Animal Sciences, 2024)
The objective was to assess the agronomic characteristics and nutritional value of silages from sorghum genotypes without bmr mutation and carrying the bmr mutation. A total of 14 genotypes were used, 7 of which were conventional (BRS 655, BRS 658, BRS 659, BRS 610, VOLUMAX, 156x947216 and 156x947030) and 7 carrying the bmr6 gene (2014F15641, 2014F15645, 2014F15649, 2014F15653, 2014F15661, 2014F15681 and 2014F15685). The experimental design consisted of randomized blocks – 4 blocks and 14 treatments, totaling 56 experimental plots. The means of the variables were subject to ANOVA through SISVAR; when significant was found, the treatments were compared using the Scott-Knott test at a 5% probability level. There was a difference (p < 0.05) for flowering days and height between genotypes. As for crude protein, mean levels ranged from 11.10 to 14.66% for 2014F15645 and BRS 610. Regardless of the mutation, there was no difference (p > 0.05) between the genotypes carrying the mutation and those not carrying the mutation for lignin and in situ dry matter digestibility. Genotypes BRS 655, BRS 658, BRS 659, BRS 610, VOLUMAX, 2014F15645, 2014F15649, 2014F15661, 2014F15681 and 2014F15685 are more suitable for silage production, as they present higher dry matter production. Regarding ISDMD, all genotypes can be used for silage production.